Remodeling of Cell-Cell Junctions in Arrhythmogenic Cardiomyopathy - Asimaki, Angeliki (Cell Commun Adhes, 2014)
Arrhythmogenic cardiomyopathy (AC) is a primary myocardial disorder characterized by a high incidence of ventricular arrhythmias often preceding the onset of ventricular remodeling and dysfunction. Approximately 50% of patients diagnosed with AC have one or more mutations in genes encoding desmosomal proteins, although non-desmosomal genes have also been associated with the disease. Increasing evidence implicates remodeling of intercalated disk proteins reflecting abnormal responses to mechanical load and aberrant cell signaling pathways in the pathogenesis of AC. This review summarizes recent advances in understanding disease mechanisms in AC that have come from studies of human myocardium and experimental models.